2020
DOI: 10.1098/rsta.2019.0325
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sources of fine particulate matter in China

Abstract: Fine particulate matter has been a major concern in China as it is closely linked to issues such as haze, health and climate impacts. Since China released its new national air quality standard for fine particulate matter (PM 2.5 ) in 2012, great efforts have been put into reducing its concentration and meeting the standard. Significant improvement has been seen in recent years, especially in Beijing, the capital city of China. This paper reviews how China understands its sources of fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…The large increases in emissions of all primary pollutants in South and East Asia have been widely reported and described by Zheng et al [106]. Air quality in Asian megacities shows values for PM, SO 2 and NO 2 in episode conditions that are similar to the highly polluted atmosphere of London in the smog episodes of the 1950s, for example the Beijing ‘haze’ events in January 2012.…”
Section: –2020 Air Quality Globallymentioning
confidence: 83%
“…The large increases in emissions of all primary pollutants in South and East Asia have been widely reported and described by Zheng et al [106]. Air quality in Asian megacities shows values for PM, SO 2 and NO 2 in episode conditions that are similar to the highly polluted atmosphere of London in the smog episodes of the 1950s, for example the Beijing ‘haze’ events in January 2012.…”
Section: –2020 Air Quality Globallymentioning
confidence: 83%
“…Air pollution from PM 2.5 (fine particulate matter with a mass median aerodynamic diameter <2.5 μm) has been estimated to cause millions of premature deaths annually in recent years ( 1 , 2 ). Therefore, mitigating PM 2.5 pollution is a high priority for environmental protection in many countries such as China ( 3 ), India ( 4 ), the United States ( 5 ), and the member states of the European Union (EU) ( 6 ). The most cost-effective abatement measures need to be identified to balance environmental protection and economic development.…”
mentioning
confidence: 99%
“…When the number of iterations reached 900, the performance of the algorithm approached saturation. Finally, the multivariate nonlinear regression model was completely fitted after 1081 iterations as PM 2.5 =68.7672e (−0.0001×Visibility) + 8.3784e (0.0029×Wind direction) − 0.0536e (0.7548×Wind speed) + 7.3861e (−0.256×RH) (18) In the training of neural network models, validation is not required due to the use of the Bayesian regularization method. Therefore, the PM data and meteorological parameters were randomly divided into two sets as: 60% for training, and 40% for a completely independent test.…”
Section: Models Trainingmentioning
confidence: 99%
“…The mission's payload is the tropospheric monitor, which measures key atmospheric constituents, including ozone, nitrogen dioxide, sulphur dioxide, carbon monoxide, methane, nitrous oxide, and Ultraviolet aerosol index [16]. At the same time, ground based direct samplers were developed to accurately measure PM concentrations [17,18]. Zhang et al [19] demonstrated how vertical wind shear affects ground-level PM 2.5 by using radar wind profiler observations in Beijing, providing new insights into the role of vertical wind shear in modulating the variation of PM 2.5 , which is worth considering in future air quality predictions.…”
Section: Introductionmentioning
confidence: 99%